COMMONWEALTH OF VIRGINIA STATE CORPORATION COMMISSION RICHMOND, JUNE 1,1999 CERTIFY THE CERTIFICATE OF INCORPORATION OF TOBACCO INDUSTRY LABOR/MANAGEMENT COMMITTEE (Tufts Archival Research Center, 2007)
Certificate of incorporation for Tobacco Industry Labor Management Committee (LMC) from the State of Virginia.